2020
DOI: 10.1007/s42000-020-00210-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: Background Polycystic ovarian syndrome is a common disorder characterized by clinical or biochemical hyperandrogenism and ovulary dysfunction. Female sexual dysfunction can have adverse effects on quality of life and interpersonal relationship. Methods We conducted a meta-analysis to evaluate the prevalence and severity of sexual dysfunction in women with PCOS. Results Compared to women without PCOS, those with PCOS were younger (28.90±3.11 versus 31.42±3.37 years; p<0.0001) and had higher body mass index (27.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 52 publications
4
25
0
Order By: Relevance
“…In a systematic review and meta-analysis which was conducted by Loh et al, it was shown that women with PCO had 30% higher risk of having SD [ 19 ].in another systematic review and meta-analysis, Pastoor et al found lower scores in the arousal, lubrication, orgams, and satisfaction in PCO women than controls [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis which was conducted by Loh et al, it was shown that women with PCO had 30% higher risk of having SD [ 19 ].in another systematic review and meta-analysis, Pastoor et al found lower scores in the arousal, lubrication, orgams, and satisfaction in PCO women than controls [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, endometriosis and PCOS are both associated with pelvic pain [ 117 , 118 , 119 ]; they also have similar pathological causes (e.g., obesity and oxidative stress) and contribute to the increased risk of cancer development in the endometrium [ 120 , 121 ]. Sexual difficulties resulting from pain during intercourse are another major complaint of patients with PCOS [ 122 , 123 , 124 ], and they are typical symptoms of endometriosis. Relative to healthy individuals, patients with PCOS are more likely to develop chronic-pain-related and neuropathic-pain-related conditions such as migraine [ 27 ], fibromyalgia [ 107 ], rheumatoid arthritis [ 125 ], and irritable bowel syndrome [ 126 , 127 , 128 ]; thus, PCOS is a potential risk factor for the increased prevalence of pain-related conditions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…FSD is associated with obesity, metabolic syndrome and androgen excess, which are commonly seen in women with PCOS 22 . Although some studies reveal a higher prevalence of FSD in women with PCOS, concerns persist around the methodological quality of the literature available 23 …”
Section: Introductionmentioning
confidence: 99%
“…22 Although some studies reveal a higher prevalence of FSD in women with PCOS, concerns persist around the methodological quality of the literature available. 23 The UK National Institute of Health and Care Excellence guidelines recommend that healthcare professionals ask patients with PCOS about emotional well-being and concerns regarding body image during consultations. However, the guidelines lack tailored advice and instead provide signposts to generalised eating disorders, which may contribute to the underestimation of emotional distress in PCOS sufferers.…”
Section: Introductionmentioning
confidence: 99%